Sosialisasi Pencegahan Stunting Dan Pemberian Makanan Tambahan (PMT) Oleh Mahasiswa KKN Universitas Riau Di Desa Sungai Batang, Kecamatan Bengkalis, Kabupaten Bengkalis - Ufira Isbah; Yola Yuliawita; Lola Melan Sihombing; Juwita Halcyon Eliani Sirait; M. Arya Janitra; Novi Aprilia; Khaila Meishafa; Muhammad Bintang Nugraha; Nurul Hidayah Sulaiman; Citra Taulani; Willy Ahmadi (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Stunting is a chronic nutritional problem found in toddlers, which is characterized by height that is not the same (short) as children of the same age. Therefore, Riau University KKN students aim to help and reduce or prevent stunting which can affect the process of growth and development of children, especially in Sungai Batang Village, Bengkalis District, Bengkalis Regency. The method of implementing activities carried out during KKN in Sungai Batang Village is as follows. 1. Initial Planning Stage, holding a meeting with the head of the posyandu to request data on how many children are affected by stunting 2. Preparation Stage, namely preparation for socialization such as cleaning the place for the event and preparing the tools and materials used such as installing banners, snacks, tables, chairs, soundsystem, and others. 3. Implementation Stage, on July 25, 2023 carrying out stunting socialization the event began with the delivery of material about stunting provided by KKN students, followed by material provided by midwives. This socialization activity was carried out at the same time to establish a relationship with the village community, especially in Sungai Batang Village. The activity continued with health checks by the posyandu which is specifically for the elderly. The distribution of additional food is also a series of activities carried out by KKN students in the Stunting Prevention Socialization Program carried out by Riau University KKN students directly. The Sungai Batang village community received education about Stunting Prevention, not only that, the provision of additional food (PMT) was also carried out to support nutritional growth for children and pregnant women.